Revija Pravnik - nekoč in danes - Koritnik, Boštjan (Pravnik, 2024)
Pravnik magazine is the oldest Slovenian professional and scientific journal, with its origins tracing back to 1862. It began with the publication of Slovenski pravnik (Slovenian Jurist), initially published by J.R. Razlag, PhD). Slovenski pravnik continued intermittently until 1888, when the society Pravnik (Jurist) took over as the publisher. The Association of Law Societies of Slovenia revived the journal after the interruption due to the World War II. From l January 1965, it has been published as Pravnik - A Journal for Legal Theory and Practice. In 2016, the Faculty of Law of the University of Ljubljana became a co-publisher. Since 2008, the journal’s editor-in-chief has been Professor Emeritus at the University of Ljubljana Dragica Wedam Lukić, PhD. The journal is included in several international bibliographic databases and receives co-funding by the Public Agency for Scientific Research and Innovation of the Republic of Slovenia (ARIS).
Keywords: ARIS; Association of Law Societies of Slovenia; Faculty of Law of the University of Ljubljana; journal; journalism; law; Pravna fakulteta Univerze v Ljubljani; pravne revije; Pravnik; pravo; publicistika; Zveza društev pravnikov Slovenije